AB0198 Cilengitide Modulates Pulmonary Cell Proliferation in the Reactive Oxygen Species Murine Model of Systemic Sclerosis. (10th June 2014) - Bagnato, G.; Bitto, A.; Irrera, N.; Pizzino, G.; Roberts, W.N.; Altavilla, D.; Squadrito, F.; Saitta, A.; Bagnato, G.
Abstract : Background: Systemic sclerosis (SSc) is a complex, multisystem rheumatic disease in which autoimmunity, inflammation, fibrosis and vasculopathy lead to a complex pattern of organ-based complications with high mortality and morbidity. In this setting a pivotal role is exerted by fibroblasts and their function is strongly influenced by the interaction with the surrounding extracellular matrix and mediated via cell surface integrins [1]. Pulmonary T cells of patients affected by SSc with interstitial lung disease expresses alphaVbeta3 and alphaVbeta5 integrins and in an animal model of lung infiltration of T lymphocytes the alphavbeta3 and alphavbeta5 integrins are required for lymphocytic infiltration and collagen accumulation in the animal model [2]. Integrins provide cells with the ability to sense their microenvironment, are constitutively expressed on fibroblasts in SSc and the expression of alphavbeta5 induces myofibroblasts differentiation of dermal fibroblasts [3]. Objectives: The aim of the study is therefore to evaluate the effect of the alphavbeta3 and alphavbeta5 inhibitor (cilengitide) on pulmonary cell proliferation in the HOCl-induced murine model of systemic sclerosis. Methods: Chronic oxidant stress SSc was induced in BALB/c mice by daily s.c. injections of HOCl for 6 weeks. 25 Mice were randomized in three arms: HOCl (n=10), HOCl plus Cilengitide (n=10) or vehicle alone (n=5). Treatment with cilengitide 20 (mg/kg/i.p./day) was started four weeks after the administration of HOCl and maintained throughout the remaining experimental period (2 weeks). Lung concentrations of cyclin D and the inhibitor p16 were evaluated by western blot analysis. Results: Pulmonary concentrations of cyclin D were significantly higher in the HOCl group compared to controls (p<0.001) and this increase was significantly reduced in mice treated with cilengitide (p<0.001). Consistently the concentrations of the cyclin D inhibitor p16 were significantly lower in HOCl compared to controls (<0.001) and increased in the group of mice treated with cilengitide (<0.001). Conclusions: Many cellular and molecular pathways are under investigation as potential targets for systemic sclerosis therapy. Cell-matrix interactions are a prominent feature of SSc pathogenesis and the results on the cyclin D pathway suggest that the inhibition of integrins function reduce pulmonary cell proliferation. Further confirmatory results are needed to better assess the specific effect of cilengitide on myofibroblasts differentiation and cell recruitment at the site of injury. References: Eckes B, Zigrino P, Kessler D, Holtkotter O, Shephard P, Mauch C, et al. Fibroblast matrix interactions in wound healing and fibrosis. Matrix Biol 2000;19:325–32. Luzina IG, Todd NW, Nacu N, Lockatell V, Choi J, Hummers LK, Atamas SP. Regulation of pulmonary inflammation and fibrosis through expression of integrins alphaVbeta3and alphaVbeta5 on pulmonary T lymphocytes. Arthritis Rheum. 2009 May;60(5):1530-9. Asano, Y., Ihn, H., Yamane, K., Jinnin, M. & Tamaki, K: Increased expression of integrin αvβ5 induces the myofibroblastic differentiation of dermal fibroblasts. Am. J. Pathol. 168, 499–510 (2006). Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5144